2009
DOI: 10.1038/ja.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic macrolide FD-891 induces caspase-8-dependent mitochondrial release of cytochrome c and subsequent apoptosis in human leukemia Jurkat cells

Abstract: The 16-membered macrolide FD-891 exerts cytotoxicity toward several cancer cell lines. In this study, we showed that FD-891 induces apoptosis in various human cancer cell lines. Human leukemia Jurkat cells were highly sensitive to FD-891, exhibiting caspase activation and mitochondrial release of cytochrome c into the cytosol at early time points after exposure to FD-891. By contrast, Jurkat cells deficient in caspase-8 were resistant to FD-891-induced apoptosis and manifested little induction of cytochrome c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Among various human cancer cell lines, four leukemia cell lines, HL-60, Jurkat, THP-1, and U-937 were highly sensitive to FD-891. [2] Further biochemical studies of FD-891 in Jurkat cells suggested that FD-891 strongly induces apoptosis of Jurkat cells through mitochondrial release of cytochrome c as well as caspase-9 processing triggered by caspase-8 activation. This apoptosis-signaling pathway caused by FD-891 was thus distinct from the other caspase-dependent apoptosis by chemotherapic drugs such as doxorubicin, etoposide, and vincristine.…”
Section: Introductionmentioning
confidence: 99%
“…Among various human cancer cell lines, four leukemia cell lines, HL-60, Jurkat, THP-1, and U-937 were highly sensitive to FD-891. [2] Further biochemical studies of FD-891 in Jurkat cells suggested that FD-891 strongly induces apoptosis of Jurkat cells through mitochondrial release of cytochrome c as well as caspase-9 processing triggered by caspase-8 activation. This apoptosis-signaling pathway caused by FD-891 was thus distinct from the other caspase-dependent apoptosis by chemotherapic drugs such as doxorubicin, etoposide, and vincristine.…”
Section: Introductionmentioning
confidence: 99%
“…[1] FD‐891 ( 1 ) shows potent cytotoxicity against leukemia cells, including HL‐60, Jurkat, THP‐1, and U‐937 cell lines [2] . The compound induces apoptosis of Jurkat cells by inducing mitochondrial release of cytochrome c and triggering caspase‐9 processing by activating caspase‐8 [2b] . It has also been proposed to induce apoptosis by the cell‐cycle arrest at the G 2 /M phase [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Their structures were first proposed to be 18-membered macrolides , but were later reassigned as 16-membered macrolides by Eguchi et al., as shown in Figure A . These macrolides have been reported to show several biological activities, , including cytotoxic activity against several tumor cell lines, when used at ten nanomolar for FD-891, 1 , and micromolar for FD-892, 2 , concentration ranges. Thus, FD-891, 1 , shows more than 100 times the potency of FD-892, 2 .…”
mentioning
confidence: 99%